2013
DOI: 10.1016/j.ympev.2013.04.034
|View full text |Cite
|
Sign up to set email alerts
|

Utility of COI, CAD and morphological data for resolving relationships within the genus Sarcophaga (sensu lato) (Diptera: Sarcophagidae): A preliminary study

Abstract: Dowton, M. (2013). Utility of COI, CAD and morphological data for resolving relationships within the genus Sarcophaga (sensu lato) (Diptera: Sarcophagidae): a preliminary study. Molecular Phylogenetics and Evolution, 69 (1), 133-141. Utility of COI, CAD and morphological data for resolving relationships within the genus Sarcophaga (sensu lato) (Diptera: Sarcophagidae): a preliminary study AbstractCurrently there are ∼3000 known species of Sarcophagidae (Diptera), which are classified into 173 genera in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 25 publications
1
20
0
1
Order By: Relevance
“…Sarcorohdendorfia ), or polyphyletic as the species are scattered on various branches of the tree ( Lioproctia , Pandelleisca ). This is in agreement with current morphological and molecular evidence of nonmonophyly in particular for Sarcorohdendorfia and Lioproctia (Pape & Kurahashi, ; Meiklejohn et al , ). Noteworthy is also the position of species of subgenus Neobellieria within Sarcophaga s.l ., in a clade comprising most native North American species of Sarcophaga (except S. aldrichi Parker and S .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Sarcorohdendorfia ), or polyphyletic as the species are scattered on various branches of the tree ( Lioproctia , Pandelleisca ). This is in agreement with current morphological and molecular evidence of nonmonophyly in particular for Sarcorohdendorfia and Lioproctia (Pape & Kurahashi, ; Meiklejohn et al , ). Noteworthy is also the position of species of subgenus Neobellieria within Sarcophaga s.l ., in a clade comprising most native North American species of Sarcophaga (except S. aldrichi Parker and S .…”
Section: Discussionsupporting
confidence: 92%
“…With node support values generally on the low side and the identities of several terminal taxa in need of verification, it can be difficult to assess when unexpected topologies are sufficiently reliable to warrant changes in the subgeneric classification. Sarcophaga alcicornis Hardy is placed in the subgenus Lioproctia by Pape () and Meiklejohn et al (), but was shown to be better corroborated as a member of subgenus Sarcorohdendorfia by Meiklejohn et al (). This finds support in our analysis and we have listed the species accordingly.…”
Section: Discussionmentioning
confidence: 98%
“…However, in the latter study, a multilocus barcode composed of COI and ITS2 resolved all species in a NJ tree and successfully identified all specimens to species using the BCM approach. The use of combined datasets, including both multilocus and morphological strategies for phylogenetic analyses is proposed in order to identify those species which remain unclear, as was suggested for other dipteran families, such as Muscidae ( Renaud et al 2012 ) and Sarcophagidae ( Meiklejohn et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Giroux et al., ; Piwczyński et al., ), these faunas have usually been treated separately (i.e. Stamper et al., ; Meiklejohn et al., ), or suffered from lack of data for Afrotropical species (i.e. Piwczyński et al., ).…”
mentioning
confidence: 99%
“…In both these studies identification success was very high using the standard barcode region. Meiklejohn et al (2013) used molecular data from COI and carbamoyl phosphate synthetase (CAD) to study the phylogenetic relationships of mainly Australian species of Sarcophaga, revealing several conflicts between their molecular and morphological phylogenies.…”
mentioning
confidence: 99%